SUITABILITY OF DIFFERENT VARIETIES OF CARROT ROOTS (DAUCUS CAROTA L.) FOR PROCESSING - Abdullaev Ilhom Eshkurbanovich; Rakhmanov Ergash Asadullaevich; Choriyev Alikul Jumaevich; Amanov Nurbek Mukhiddinovich (Galaxy International Interdisciplinary Research Journal, 2022)
The results of studying the efficiency of the production of dry products of carrots grown in the conditions of the desert soil-climatic zone of the Surkhandarya region, depending on the variety, are presented. A comprehensive assessment of fresh and dried carrot products of 22 different varieties was carried out in terms of the content of the main economic biological indicators in order to select the most suitable for drying. Varieties have been identified, the root crops of which are characterized by high yields, have the highest marketability, accumulate more dry matter, sugars, and the like.